Marine technology education for the changing Malaysia : the role of marine technology laboratory at Universiti Teknologi Malaysia - Ahmad, Mohd. Zamani; Abdul Mukti, Mohd. Afifi (Faculty of Mechanical Engineering, 1998)
Malaysia is changing fast towards becoming a nation that possesses comparative economic and industrial advantage base on engineering talent. Central planning includes improving its education and research programmes. The development of the Marine Technology Laboratory at Universiti Teknologi Malaysia is part of such programme to support the national maritime engineering sector. The paper captures the dynamic change of the marine technology education curricula since its inception in the early eighties and the role of the laboratory in harnessing the curricula to make it more relevant, attractive and connected.